Understanding the factors which enable and hinder the academic head of department in their ability to be effective in people management - Hill, Sandy (Organisational Psychology, 2020)
The aim of this study was to first identify which competencies are important to enable the academic Head of Department (HOD) to be more effective in people management, and secondly, to understand the factors which hinder the HOD in achieving this important function of the role. The HOD is pivotal to the running of an effective university in that he or she ensures the academic discipline is well-functioning and successfully operational. An essential requirement to do this is to manage and develop the staff employed to meet these goals. The literature on academic people management was reviewed and the results of this review produced propositions which were used as a basis for the study. To identify the important competencies, data was collected from staff reporting to HODs at the University of Cape Town (UCT) via way of an online questionnaire. To gain insight and understand the perceptions and perspectives of HODs, a qualitative research approach and an interpretative phenomenological inquiry-based research design was used, and data was collected via semi-structured interviews. The data was analysed, making it possible to identify whether the propositions made via reviewing the literature, were able to be supported. A summary of the key findings and a discussion of what needs to be considered for effective people management by HODs at UCT is presented. Recommendations for further studies conclude the dissertation.